Perencanaan Strategis Sistem Informasi pada Perusahaan Jasa Ekspedisi PT. X - Tantra, Danny; Kendengis, Yulia; Santoso, Leo Willyanto (Jurnal Infra, 2015)
PT. X is n new express delivery company which was established in 2010 and still using the traditional business system. PT. X needs information system strategy and information technology (IT) to support its business processes so it can survive and compete in this modern business world. The information system strategy and IT that will be applied adjusted to the vision, mission, companyâs strategic, and companyâs need.In effort to produce information system strategic and the IT for PT. X analysis is performed using information system strategic planning which is started with porter value system analysis methods, strength, weakness, opportunities, and threat analysis (SWOT), and TOWS analysis. Finally, the analysis is continued using balanced scorecard analysis (BSC) and critical success factors (CSF).From the research conducted, informations about the companyâs conditions, companyâs needs, and the companyâs competitive forces are produced. The companyâs CSF can also be known from this research. In the end of this research the most suitable aplication portfolio with the companyâs vision mision, strategy, and companyâs need are produced for the PT. X.